Pengaruh Model Pembelajaran Guided Discovery Terhadap Sikap Ilmiah dan Hasil Belajar Siswa pada Materi Biologi Kelas X - Haslinar, Haslinar; Daud, Firdaus; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2022)
Abstract. This research is a true-experimental research with posttest-only control group design which aims to determine the effect of guided discovery learning model on learning outcomes and scientific attitudes of class X students. The independent variable in this study is the learning model, while the dependent variable is learning outcomes and scientific attitudes. The samples of this study were students of MA Negeri 2 Soppeng class X MIA which were selected by random sampling with 15 students from class X MIA1 as the experimental class, and 15 students from class X MIA2 as the control class. The research data were obtained by giving posttest learning outcomes tests in the form of multiple choices to see student learning outcomes and a Likert scale questionnaire containing statements to see students' scientific attitudes. The data analysis technique is the independent sample T test. Based on the results of inferential statistics, the significance value (2-tailed) was 0.001, which was smaller than =0.05 for learning outcomes and the significance value (2-tailed) was 0.000, which was smaller than =0.05 for scientific attitudes. It can be concluded that the application of guided discovery learning has an effect on student learning outcomes and scientific attitudes.Keywords: learning outcomes, scientific attitude, guided discovery, a true-experimental, posttest.